PENGGUNAAN DIKSI DALAM PENULISAN MAKALAH PADA MAHASISWA JURUSAN PENDIDIKAN AKUNTANSI - HALIMATUSSAKDIAH HALIMATUSSAKDIAH; GRACE SITUMORANG (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2013)
ABSTRACTThe writing of this article was distributed by the author's observations with regard to the use of the word diction in term paper writing. The article is titled “201CPenggunaan Diction in the writing Paper on Students majoring in accounting education in the regular class B 2011”. The writing is also effected by the author's curiosity towards the knowledge and ability of students in its diction in term paper writing term paper, either individual or group papers. It is also given that the student who is always dealing with paper writing in courses. In the writing of the paper, authors of papers should be able to choose and place the appropriate word to be used in writing the paper. Things that are going to be sosotan the author of this research in the mini. The object in this research was a paper written by University students majoring in accounting education in the regular class B Faculty of Economics State University of Medan. The paper in question was completed by a working group or individual. The purpose of this research is the mini-writing to find out how the level of proficiency in the use of diction student in the writing of term papers. The Data collected by the author with regard to the writing of this research comes from the mini papers completed by students majoring in accounting education B.Key Words: Papers, Students, Diction.